Patterns for emerging application integration scenarios: A survey. (July 2017) - Ritter, Daniel; May, Norman; Rinderle-Ma, Stefanie
Highlights: Analysis of the discipline of enterprise application integration with a focus on integration patterns (i.e., enterprise integration patterns (EIP) from 2004) in the context of emerging trends (e.g., Cloud- and Mobile Computing, IoT, Big Data) and new requirements (e.g., processing styles like streaming, (stateful) conversations, scalability) in 2017. A systematic literature review of the coverage as well as solutions for these new trends and aspects between 2004 and now, to answer questions around the evolution of the discipline from a research perspective. An analysis of the most influencial EAI system implementations (i.e., commercial, startup, and open-source) to cross-check the divergence between research and practical solutions required to address the trends and aspects in real-world systems. The proposal of a more systematic description of the new, but rather ad-hoc real-world solutions as patterns (complementary to the EIP) by example of a "design for scalability" trade-off. The design of a pattern catalog for currently missing patterns in literature, for which solutions were found in the system review. An evaluation of the usage of the original EIP and the newly found patterns as part of integration scenarios in a well-established cloud integration system in form of a quantitative analysis based on a new content monitor pattern implementation. Abstract: The discipline of enterprise application integration (EAI) enables the decoupled communication between (business) applications, and thus became a cornerstone of today's IT architectures. In 2004, the book by Hohpe and Woolf on Enterprise Integration Patterns (EIP) provided a fundamental collection of messaging patterns, denoting the building blocks of many EAI system implementations. Since then, multiple new trends and a broad range of new application scenarios have emerged, e. g., cloud and mobile computing, multimedia streams. These developments ultimately lead to conceptual changes and challenges such as larger data volumes (i. e., message sizes), a growing number of messages (i. e., velocity) and communication partners, and even more diverse message formats (i. e., variety). However, the research since 2004 focused on isolated EAI solutions, and thus a broader and integrated analysis of solutions and new patterns is missing. In this survey, we summarize new trends and application scenarios which serve as a frame to structure our survey of academic research on EIP, existing systems for EAI and also to classify integration patterns from these sources. We evaluate recently developed integration solutions and patterns in the context of real-world integration scenarios. Finally, we derive and summarize remaining challenges and open research questions.